Ecology and management of tropical secondary forest: Science, people, and policy - Guariguata, Manuel R. Finegan, Bryan (1998)
Research in tropical forestry is confronted with the task of finding strategies to alleviate pressure on remaining forests, and techniques to enhance forest regeneration and restore abandoned lands, using productive alternatives that can be attractive to local human populations.